The Identity of Catholic Higher Education - Patrick, Patrick Valdrini (Prawo Kanoniczne, 2024)
The author conducts a broad analysis of the identity of Catholic education, identifying the legal foundations for the operation of ecclesiastical and Catholic universities. He then demonstrates the role of ecclesiastical teachings in the context of Catholic education and their role in shaping the identity of Catholic universities, recognizing their significant contribution to the good of society and pointing out that universities are unique places for experiencing community.